2021
DOI: 10.1177/03000605211006661
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of common causes of liver damage among children 12 years and younger in Weifang

Abstract: Aims To explore the causes of liver damage among children 12 years and younger in Weifang and to provide a theoretical basis for early diagnosis of liver damage in children. Methods Retrospective study of clinical data from pediatric patients (age ≤12 years) with liver damage in diagnosed at Weifang People's Hospital from June 2010 to May 2020. Results A total of 2632 children (1572 boys, 1060 girls) aged ≤12 years were diagnosed with liver damage including infectious liver damage (2100 cases), non-infectious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The symptoms can vary greatly, with a range of presentations including asymptomatic elevation in aminotransferases, cholestasis, acute liver failure, hepatic fibrosis, and cirrhosis ( 18 ). Consistent with prior research conducted in another region of China ( 19 ), infection remained the most common entity encountered, especially EBV and CMV infections in this study. CMV hepatitis is predominantly seen in young infants, whereas EBV hepatitis is predominantly seen in children over 1 year of age.…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms can vary greatly, with a range of presentations including asymptomatic elevation in aminotransferases, cholestasis, acute liver failure, hepatic fibrosis, and cirrhosis ( 18 ). Consistent with prior research conducted in another region of China ( 19 ), infection remained the most common entity encountered, especially EBV and CMV infections in this study. CMV hepatitis is predominantly seen in young infants, whereas EBV hepatitis is predominantly seen in children over 1 year of age.…”
Section: Discussionsupporting
confidence: 92%
“…Biliary atresia is the commonest primary aetiology requiring LT in children across the world. Among the rest, autoimmune liver disease, metabolic and genetic liver diseases such as Wilson disease, progressive familial intrahepatic cholestasis and liver malignancies predominate [1,2]. Paediatric liver transplant [PLT] is demanding due to the inherent nature of smaller body proportions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the safety and efficacy of omadacycline in pediatric patients aged 8-18 years remain unclear (Burgos and Rodvold, 2019). M. pneumoniae infection and antiinfective drugs have a high tendency to cause liver and kidney impairment in pediatric patients, as the liver and kidney functions of children are not yet fully developed (Meng et al, 2021). Pharmacokinetic studies have shown that omadacycline is widely distributed in most tissues throughout the body after administration, with high plasma concentrations achieved in lung tissue.…”
Section: Discussionmentioning
confidence: 99%